THERMAL AND STRUCTURAL ANALYSIS OF BIO-DEGRADABLE PLA-BASED NANO ALUMINUM FOILS FOR HEAT DEPOSITION (International Journal of Food and Nutritional Sciences, 2023)
One of the biggest worldwide environmental challenges of our day is the creation of natural and biodegradable materials based on biodegradable food packaging materials. But using bio-based packaging materials, including food-grade or biodegradable films made from recycled materials, might at least partially solve the waste issue. Thus, consistency and freshness of items may be maintained for the duration needed to be advertised and utilised with the right product selection and packaging technique. Despite this, the market's supply of bio-based food packaging is restricted because of its poor mechanical and gas barrier qualities. In their study, they use Ansys 2020 R1 to examine structural and thermal studies. The aluminium PLA aerofoil 3N, 6N, and 9N, as well as the applied temperatures of 120C, 360C, 400C, and 500C, were studied. Lastly, to compare the verified outcomes.